Pengembangan potensi ekowisata untuk meningkatkan perekonomian masyarakat Desa Mempura Kabupaten Siak di masa Pandemi Covid-19 - Cisilia Maiyori (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The Siak Regency Government's policy to close the tourist attraction of the Siak Sri Indrapura Royal Palace to prevent the spread of the Covid-19 outbreak has an impact on the economy of the community, including the people of Mempura Village. This service aims to help develop ecotourism potential to improve the economy of the Mempura Village community during the Covid-19 pandemic. The method of implementation used in this service activity uses the lecture method accompanied by direct dialogue with the community. Siak Regency has been known to the public, both nationally and internationally, with the tourist attraction of the Siak Sri Indrapura Royal Palace which is famous for its glory and historical heritage that is thick with Malay cultural features that blend Islamic nuances. In fact, apart from historical tourism, the beautiful and luscious landscape of Siak Regency has the potential to become a promising ecotourism area. Especially when people's economic conditions are deteriorating due to the Covid-19 pandemic that has hit during the last few months. The effort made by the service team is to provide legal counseling on ecotourism to help the community develop the potential for ecotourism in Mempura Village. In developing an ecotourism area, real support from the Siak Regency Government is needed as a form of the government's support for improving the community's economy